Community radio and grassroots democracy: a case study of three villages in Yogyakarta Region, Indonesia - Birowo, Mario Antonius (Curtin University, 2010)
It has been argued that the most important factor in creating participation for people at grassroots level is accessibility to the media, both as receivers and producers of content (see Rodriguez, 2000; Fraser & Estrada, 2001, 2002; Tabing, 2002; and Dagron, 2001, 2004). In recent years, community radio stations have been mushrooming in Indonesia as a consequence of the democratisation of the media system in post-Soeharto Indonesia. In Indonesia community radio is used by the civil society at grassroots level to empower people who have little opportunity to voice their interests. The characteristics of community radio - size, proximity and openness to participation - provide both forms of access. By providing a forum for capacity building, community radio enhances people’s participation in the decision making process and in the preservation of local cultures in their villages. In fact, at village level the empowerment of people is central to the role of community radio; thus, people in Timbulharjo, Minomartani and Wiladeg have had the opportunity to express their interests. Community radio stations encourage diversity, challenging the tendency of commercial radio to erase cultural differences through their conceptualising of audiences as markets. In this way, community radio accommodates the interests of marginal social groups and draws them into the public sphere.This thesis is about the way in which the Indonesian people’s movement creates grassroots democracy by using community radio as a tool for participating in social communication processes at village level, in particular in Yogyakarta Special Region. The main question is ʻhow do people at grassroots level use community radio in the democratic transition in Indonesia?’ Multiple case studies were used in order to build a comprehensive picture of the use of community radio in Indonesia as a tool for promoting participation in local contexts. To discuss its findings this thesis uses participatory communication and public sphere theories. This thesis also considers the civic role of community radio in its responses to earthquake disaster in several regions in Indonesia, where people used the medium of radio to create solidarity to help affected people.